Hypercapnic ventilatory response in heart failure patients with central sleep-disordered breathing. (25th November 2020) - Roder, F; Potratz, M; Sohns, C; Rudolph, V; Fox, H
Abstract: Background: Sleep-disordered breathing (SDB) is a highly common comorbidity in heart failure (HF) patients and appears mainly as obstructive SDB, or central SDB. SDB has been shown to deteriorate quality of life in HF patients, but its presence is also associated with worse prognosis. SDB severity has been shown to mirror HF level and hereby hypercapnic ventilatory response (HCVR) depicts ventilation instability which furthermore expresses HF severity. But HCVR direct correlation with HF to predict HF severity has not been sufficiently studied yet. Methods and results: We included 501 HF patients that received multichannel cardiorespiratory polygraphy, clinical workup for HF and HCVR in our center. The degree of SDB was graded with apnea-hypopnea-index (AHI) with guideline recommendation for treatment at an AHI >15/h. NT-Pro-BNP was obtained for HF quantification. Mean age was 66.4±11 years, body mass index (BMI) 30.7±5 kg/m 2 and mean HCVR was 2.56±1.18. 136 (27.2%) patients had central SDB with a proportion of 124 (24.8%) having moderate to severe SDB (AHI >15/h). 345 (68.9%) had obstructive SDB with moderate to severe SDB in 296 (59.1%) patients. Differences were detected for HCVR and HF in the central SDB group with a HCVR of 2.78±1.4 and NT-Pro-BNP of 2835.88±10536.4 pg/ml, while the OSA group shows a HCVR of 2.5±1 and NT-Pro-BNP of 929.9±1781. Linear regression identified HCVR (p=0.045) and NT-Pro-BNP (p=0.034) to independently correlate with central SDB and in addition HCVR was also significantly associated with NT-Pro-BNP (p=0.007). Conclusion: HF severity is closely linked to both NT-Pro-BNP and central SDB. HCVR seems to have the potential to predict manifestation of central SDB and increased NT-Pro-BNP values in HF. HCVR may be an easily obtainable parameter to identify both HF severity and presence of central SDB in HF patients. Funding Acknowledgement: Type of funding source: None